Asessing Parenting Education: Parenting Styles Of Adolescents In Rural And Urban Society - Nurkholida, Erna; Hakim, Mukhammad Luqman (Indonesian Journal of Educational Studies, 2020)
The objective of this study is to find out the differences of parenting styles in rural and urban society toward with adolescent’s involvement in family decision making. This research using a cross sectional survey method and embracing the theories of Montessori, Steinberg and Santrock about adolescent development, and Yusuf in parenting styles. The instrument used was adapted from the Alabama Parenting Questionnaire. It was consisted of 13 questions they were independency, responsibility, honesty, self-acceptance, receiving mistakes, trust, protection, freedom, involvement, and discipline. The result of rural society was the highest maximum value on the acceptance question (59%), namely admitting mistakes. For urban society data showed that the highest score of the questionnaire is about the parenting style of acceptance with a value of 62%. This meant that the result of the parenting style the child receives was the permissiveness style of care. The conclusion based on the area the urban society is more democratic in parenting. It makes teenagers more independent, confident and open minded